Analysis Physicochemical and In Vitro Antibacterial Activity of White Pomegranate Peel Extract (Punica granatum L.) - Azizah, Nur; Ma'rifah, Shofia Jannatul; Jamilah, Zahrotul; Syarivah, Thoifatus; Harmono Putri, Nabiilah Rifda; Ramadhan, Majida; Faisal (Biotropika: Journal of Tropical Biology, 2026)
Antibacterial agents from natural biological compounds can originate from phenolic compounds found in plants, including the white pomegranate fruit. However, the use of white pomegranate peel is still relatively unknown to the public, so it is often discarded, even though this part contains phenolic compounds and flavonoids that have potential as natural antibacterial agents. This study aimed to analyse the physicochemical characteristics of white pomegranate peel extract (Punica granatum L.) and evaluate its antibacterial activity against Staphylococcus aureus and Escherichia coli. Peak absorption, wavelength, and functional groups were analysed using UV-Vis and FTIR, while antibacterial activity was tested using the well-diffusion method. The extract was tested at concentrations of 25%, 50%, 75%, and 100% as the treatment factors. The physicochemical test results showed that the moisture content of the simplicia was 3.378%, which met the quality criteria of good simplicia, while the ash content of 19.27% indicated a fairly high mineral content. The UV-Vis spectrum showed absorption at wavelengths of 230–295 nm, indicating the presence of flavonoid compounds, while FTIR results confirmed the presence of alcohol and phenolic functional groups. Antibacterial tests showed that white pomegranate peel extract inhibited the growth of E. coli and S. aureus with the largest inhibition zones at a concentration of 100%, measuring 20 mm and 23 mm, respectively. Based on the inhibition strength category, this extract was strong against E. coli and very strong against S. aureus. Thus, white pomegranate peel extract has the potential to be developed as an effective natural antibacterial agent.